YÅ«suf Al-Qará¸ÄwÄ«'s IstinbÄá¹ Method and Its Implementation in the Moderation of Islamic Law - Yaqin, Ainol (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
This paper described the formulation of YÅ«suf al-Qará¸ÄwÄ«'s isntinbÄá¹ method towards moderate fiqh. The choice of this theme was based on the existence of two demeanours in religion, between permissive and inclusive. Two main questions in this research were, first, how did YÅ«suf al-Qará¸ÄwÄ« formulate the istinbÄá¹ method for moderate fiqh? Second, how is the implementation of this method in formulating Islamic law? This paper concluded two things through a literature study with the descriptive-analytic method. First, there were six formulations of the istinbÄá¹ method for the moderation of Islamic law. a. Examining the maqÄá¹£id contained in the text before determining Islamic law, b. Linking texts and Islamic law with texts and other Islamic laws. c. Understanding texts in the frame of asbÄb (al-nuzÅ«l or al-wurÅ«d), both micro and macro. d. Distinguishing between constant maqÄá¹£ids and changing instruments. e. Adjusting between al-thawÄbit and al-mutaghayyirÄt. f. Observing the difference between worship and muâ€™Ämalah in terms of wisdom, â€˜illah and maqÄá¹£id. Second, this method of istinbÄá¹ could produce fiqh with a flexible, elastic, dynamic, adaptive, and easy-to-practice.